Dampak Media E-Learning Terhadap Motivasi Belajar Mahasiswa Selama Pandemi COVID-19 - Yanti Arasi Sidabutar; Lisbet Novianti Sihombing; Natalina Purba (Universitas Islam Sumatera Utara, 2020)
The aim of the research was to see how the The Impact of E-Learning Media on Student Learning Motivation During the COVID-19 Pandemic. The research method used was, a quasi-experiment with One Group Pretest-Posttest. Essay tests and a motivation questionnaire are among the research instruments. The Researche use five quesetions for essay test and use twelve questions for motivation questionnaire. The showed that E-Learning media can improve learning by increasing their learning outcomes and motivation. This is shown by t-test results with sig. 0.000 and count -12.43. The application of E-Learning media improves students' motivation to learn. with a sig. of 0.000, the gives a of -14.72.